Rare bird documentation form for Northern Goshawk at Red Rock Reservoir, 1984 - Thompson, Denniset al (1984)
Rare bird documentation form for a Northern Goshawk at Red Rock Reservoir in Marion County, IA on March 18, 1984. Epson - sheet feed